2020
DOI: 10.1111/ner.13155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unilateral Subthalamic Nucleus Deep Brain Stimulation on Contralateral Subthalamic Nucleus Local Field Potentials

Abstract: Objectives Unilateral subthalamic nucleus (STN) deep brain stimulation (DBS) for Parkinson's disease (PD) improves ipsilateral symptoms, but how this occurs is not well understood. We investigated whether unilateral STN DBS suppresses contralateral STN beta activity in the local field potential (LFP), since previous research has shown that activity in the beta band can correlate with the severity of contralateral clinical symptoms and is modulated by DBS. Materials and Methods We recorded STN LFPs from 14 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Recent technical investigations into likelihood of ECG contaminations 48 showed the predominance of ECG artifacts with left-sided implants and laterality of IPG placement should be taken into consideration in future for patients with chronic sensing devices. However, although previous aDBS studies have suggested independent oscillatory activity between hemispheres 49 , other studies have demonstrated beta coupling between subthalamic nuclei 5 , 50 and even suppression of oscillatory activity in the contralateral STN during unilateral DBS 51 . Hence, even unilateral robust DBS signals might be a sufficient basis for aDBS algorithms.…”
Section: Discussionmentioning
confidence: 81%
“…Recent technical investigations into likelihood of ECG contaminations 48 showed the predominance of ECG artifacts with left-sided implants and laterality of IPG placement should be taken into consideration in future for patients with chronic sensing devices. However, although previous aDBS studies have suggested independent oscillatory activity between hemispheres 49 , other studies have demonstrated beta coupling between subthalamic nuclei 5 , 50 and even suppression of oscillatory activity in the contralateral STN during unilateral DBS 51 . Hence, even unilateral robust DBS signals might be a sufficient basis for aDBS algorithms.…”
Section: Discussionmentioning
confidence: 81%
“…Clinical evidence has shown that unilateral stimulation of the STN can produce bilateral therapeutic affects [22], albeit with reduced efficacy compared to bilateral stimulation in the contralateral side [23, 24]. Electrophysiologic recordings of the unstimulated STN revealed modulated firing rates that suggest bilateral projections of the STN [25, 26] or possible inter-connectivity [27]. This additionally may be important in epilepsy where duty cycle stimulation programming and its effect on neural networks may benefit from cross-talk between bilateral leads [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative, unilateral, high-frequency electrical STN stimulation induced and suppressed tremor in both forearms in a frequency-dependent manner, accompanied by bilateral, subthalamic, oscillatory local field potential changes ( Liu et al, 2002 ). Unilateral STN-DBS suppressed contralateral STN beta LFPs ( Hasegawa et al, 2020 ). In the animal model, neural subthalamic single unit firing rates were decreased bilaterally after unilateral STN-DBS in dopamine-depleted rats, indicating cross-talk between bilateral STN neurons ( Shi et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%